Solid–liquid separation method governs the in vitro bioaccessibility of metals in contaminated soil-like test materials. (September 2015) - Laird, Brian D.; Weiseth, Blake; Packull-McCormick, Sara R.; Peak, Derek; Dodd, Matt; Siciliano, Steven D.
Highlights: Metal bioaccessibility measured in two types of contaminated test material. Bioaccessible definitions included centrifugation, micro-, and ultra-filtration. Metal bioaccessibility similar between centrifugation and microfiltration. Lowest metal bioaccessibility observed using ultrafiltration. Ultrafiltration cutoff (3–1000 kDa) does not affect bioaccessibility. Abstract: An in vitro gastrointestinal model was used to explore the role of solid–liquid separation method on the bioaccessibility of trace elements in a smelter-impacted soil (NIST-2711) from Helena, MT and a mine overburden from an open-pit gold and silver mine in Mount Nansen, YK (YK-OVB). Separation methods studied included centrifugation (5000 g, 12 000 g ), syringe microfiltration (0.45 μm), and ultrafiltration (1000 kDa, 50 kDa, 30 kDa, 10 kDa, 3 kDa). Results indicated that the use of syringe microfiltration generally yields the same bioaccessibility as the use of centrifugation and that the speed of centrifugation does not typically affect metal bioaccessibility. However, ultrafiltration consistently yields a significantly lower bioaccessibility than the use of centrifugation and syringe microfiltration. There are rarely any differences between bioaccessibility estimates generated using a low-resistance (1000 kDa) and a high-resistance (3 kDa) ultrafiltration membrane; therefore, under the in vitro gastrointestinal conditions modeled herein, negligible quantities of trace elements are complexed to small molecules between 3 and 1000 kDa. The primary exceptions to these trends were observed for Pb in NIST-2711 (5000 g >  12 000 g >  0.45 μm > ultrafiltration) and for Tl in NIST-2711 and YK-OVB (5000 g  ∼ 12 000 g  > 0.45 μm > ultrafiltration). These results provide valuable information to researchers attempting to expand the use of in vitro bioaccessibility beyond soil Pb and As.